Life in Modern American - Peter Bromhead (Longman, 1998)
This book is a wide-ranging study of political and social life in the United States, written for advanced students of English. It examines the many factors which influence American life, including the geography of the country, the structure and working of government, the origins of the American people. It has been extensively revised to reflect the social and political changes which have take place in the late 1980s, and new photographs portraying contemporary America have been included throughout.